Analysis of Cost Benefit Services For Selling State Property (Case Study at KPKNL Sorong) - Dio Graha Putra Pangestu; Taufik Raharjo (Department of Public Administration, Muhammadiyah University of Makassar, 2021)
KPKNL Sorong has a working area covering all districts/cities in West Papua Province with an area of 102,955.15 Km2, one of the functions of the KPKNL Sorong is to provide services for the write off of BMN through sales. In serving BMN sales, it costs money to visit the location and on the other hand, benefits can be obtained by the state in the form of PNBP. The research is intended to determine the costs and benefits that can be valued in money in BMN sales services at KPKNL Sorong and to find out whether the cost and benefit analysis can be applied in services. The research used a qualitative descriptive approach with a case study research method. Quantitative data is processed with a variable costing approach, then qualitative data is processed by referring to the Miles and Huberman model. The result concludes that two proposals have negative net benefits. When combined with documented data, 10 proposals have negative net benefits. However, overall it still generated a net positive benefit of Rp. 1,304,560,098. The cost-benefit analysis has been applied internally by KPKNL Sorong, not when receiving proposals but when processing proposals. From the regulatory side, the analysis of costs and benefits that cannot be valued in money has been applied in the regulation of the write off of BMN, for benefit costs that can be valued in money allow it to be applied in the preparation of the next regulation, but a first study is needed to determine service options.KPKNL Sorong memiliki wilayah kerja meliputi seluruh kabupaten/kota di Provinsi Papua Barat dengan luas 102.955,15 Km2, salah satu fungsi KPKNL Sorong adalah menyelenggarakan pelayanan penghapusan BMN melalui penjualan. Dalam melayani penjualan BMN diperlukan biaya untuk mengunjungi lokasi dan disisi lain manfaat dapat diperoleh negara berupa PNBP. Penelitian dimaksudkan untuk mengetahui biaya dan manfaat yang dapat dinilai dengan uang dalam pelayanan penjualan BMN di KPKNL Sorong serta mengetahui apakah analisis biaya dan manfaat dapat diterapkan dalam layanan. Penelitian menggunakan pendekatan deskriptif kualitatif dengan metode penelitian studi kasus. Data kuantitatif diolah dengan pendekatan variable costing, kemudian untuk data kualitatif diolah dengan merujuk model Miles dan Huberman. Hasilnya disimpulkan terdapat dua usulan yang memiliki manfaat net negatif. Apabila dikombinasikan dengan data hasil dokumentasi, terdapat 10 usulan yang memiliki manfaat net negatif. Namun, secara keseluruhan masih menghasilkan manfaat net positif sebesar Rp.1.304.560.098. Analisis biaya manfaat sudah diterapkan secara internal oleh KPKNL Sorong, bukan saat menerima usulan melainkan saat memproses usulan. Dari sisi regulator, analisis biaya dan manfaat yang tidak dapat dinilai dengan uang sudah diterapkan dalam regulasi penghapusan BMN, untuk biaya manfaat yang dapat dinilai dengan uang memungkinkan untuk diterapkan dalam penyusunan regulasi berikutnya namun diperlukan kajian terlebih dahulu untuk menentukan opsi-opsi layanan.